Prediction of the wine price purchased using classification trees - Wise Lozano, Jorge Alberto; Arroyo, Pilar (My University, 2022)
The wine market is expected to recover and growth in the following years. Although the market size of this market is small in Mexico; efforts are being made to promote national wines. To support these actions, the current study aims to explore consumers’ decision to pay for a low versus high priced wine according to wine attributes and external influences. A total of 290 wine consumers, knowledgeable about wines, participated in an online survey that took place in the Northwest part of Mexico. The relevance that eleven attributes have on the wine price was assessed through the application of classification trees, a method that has not been previously applied to explore wine purchase decisions. The result indicate consumers are mainly driven by price than the wine attributes. However, relevant attributes for consumers of low-priced wines (less than 20 USD) include “label information” “awards” and “previous tasting”. By contrast, purchase decision of consumers of pricey wines are mainly driven by “country or region of origin” and “vineyard recognition”. The study findings offer provide suggestions on the wine attribute wineries and marketers should focus on to meet the current consumers’ preferences depending on the price-sensitivity and wine knowledge of target segments.
Vinculatégica Efan
Keywords: Vino; México; Conocedores; Consumidores de vino; Campus Mexicali